The clinical efficacy of transcutaneous electrical nerve stimulation (TENS) for acute and chronic pain: a protocol for a meta-analysis of randomised controlled trials (RCTs) - Mark I Johnson; Carole A Paley; Priscilla G Wittkopf (BMJ Open)
Introduction The aim of this systematic review with meta-analysis is to evaluate the clinical efficacy of transcutaneous electrical nerve stimulation (TENS) for any type of acute and chronic pain in adults.Methods and analysis We intend to search electronic databases (Cochrane Library, MEDLINE, Embase, CINAHL, PsycINFO, LILACS, PEDRO, Web of Science, AMED and SPORTDiscus) from inception to the present day to identify all randomised controlled trials (RCT) on the use of TENS in adults for any type of pain including acute pain, chronic pain and cancer-related pain. We will screen the RCTs against eligibility criteria for inclusion in our review. Two reviewers will independently undertake RCT selection, data extraction and risk of bias assessment. Primary outcomes will be: (i) participant-reported pain relief of ≥30% expressed as frequency (dichotomous) data; and (ii) participant-reported pain intensity expressed as mean (continuous) data. We will conduct meta-analyses to determine risk ratio for dichotomous data, and mean difference (MD) or standardised MD for continuous data for TENS versus placebo TENS, no treatment or waiting list control, standard of care, and other treatments. Subgroup analyses will include different pain conditions (eg, acute vs chronic), TENS intensity, during versus after TENS, TENS as a sole treatment versus TENS in combination with other treatments and TENS administered as a single dose versus repetitive dose.Ethics and dissemination This systematic review will not use data from individual participants, and the results will be disseminated in a peer-reviewed publication and presented at a conference.PROSPERO registration number CRD42019125054.